Perbandingan Kepuasan Pelanggan atas Pengalaman Mengikuti Kelas Yoga Daring dan Kelas Yoga Luring - Dyah Shinta Dwitya (Institut Teknologi Bandung, 2022)
Online yoga classes in various formats have seen a surge in popularity after the COVID-19 pandemic hit the world. This trend is considered to make it easier for participants and instructors, but also raises its own concerns regarding the comfort and safety of participants. Find out which options are considered more satisfying in the eyes of yoga class participants (customers): yoga classes in online or offline formats. Data collection was carried out using an online questionnaire via Google Form which was distributed via several instant messaging applications to 49 people obtained from several yoga communities. 7 respondents did not meet the inclusion criteria. Data processing to compare customer satisfaction with offline and online yoga classes was carried out using the Minitab software, using a paired t-test procedure on the answers obtained from the second and third parts of the questionnaire. Then a correlation test was carried out using the Pearson Correlation Test method to determine the correlation between customer satisfaction and the aspects examined in the questionnaire. Based on the comparative T-test conducted, a p-value of <0.05 was obtained for all aspects being compared, namely Outcome Quality (OQ), Relational Quality (RQ), Physical Environment (PE), Safety & Risks (SR), Customer Satisfaction (SAT), Word-of-Mouth (WOM), and Psychological Commitment (COM). All comparison tests obtained a higher mean score in the offline yoga class than the online yoga class. The online yoga class format has not been able to replace the conventional offline format yoga class in the eyes of the participants. The results of this study can be used as one of the considerations for involving customer satisfaction factors in determining steps that can be taken to improve the quality of yoga classes in online formats, or for further research.. Keywords: Yoga, customer satisfaction, online sports.